Fragment depicting a senior ascetic and musicians - Temples of India Project Team (Jio Institute, 2024)
This interesting fragment depicts a senior ascetic, likely a Shaiva ascetic, positioned in the extreme right corner, delivering a sermon to a lady. To his left, there appears to be his disciple showing reverence to his guru. Following them, there is a series of garland bearers and musicians facing the venerable guru. Despite some damage to the fragment, it appears that the guru is not a simple human but a divine being with four arms. He seems to be holding a snake and trident in his upper two hands. It cannot be ascertained whether the figure is Shiva delivering a sermon to a lady, possibly Parvati, or if he is Lakulisha.